The Da Vinci code : a novel - Brown, Dan, 1964- (New York : Doubleday, 2003)
Harvard symbologist Robert Langdon and French cryptologist Sophie Neveu work to solve the murder of an elderly curator of the Louvre, a case which leads to clues hidden in the works of Da Vinci and a centuries-old secret society.
850
Accelerated Reader AR
Keywords: Leonardo, -- da Vinci, -- 1452-1519 -- Appreciation -- Fiction; Art museum curators -- Crimes against -- Fiction; Secret societies -- Fiction; Cryptographers -- Fiction; Grail -- Fiction; Paris (France) -- Fiction; Mystery fiction